1986
DOI: 10.1002/ajmg.1320230128
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of autism in fifty males with the fragile X syndrome

Abstract: Fifty males with the fragile X [fra(X)] syndrome, which we consider synonymous with the Martin-Bell syndrome, were identified by a chromosome analysis of patients with developmental delays or mental retardation and family studies of known fra(X) pedigrees. These males were evaluated for autism using three criteria: 1) the DSM III diagnostic criteria for Infantile Autism; 2) the Autism Behavior Checklist (ABC); and 3) the Diagnostic Checklist for Behavior Disturbed Children, Form E2. Sixteen percent of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
0
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(128 citation statements)
references
References 30 publications
4
122
0
2
Order By: Relevance
“…The rates of stereotypy reported in the present study are in keeping with those reported in previous research (e.g. Hagerman et al, 1986). However, it is of note that the rates of SIB and aggression reported in this study are far higher than rates cited in previous research (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The rates of stereotypy reported in the present study are in keeping with those reported in previous research (e.g. Hagerman et al, 1986). However, it is of note that the rates of SIB and aggression reported in this study are far higher than rates cited in previous research (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Research has investigated the impact of comorbid ASD in FRAX by comparing individuals with comorbid ASD to those with FRAX only. Such research has reported lower IQ (Hagerman et al, 1986), greater deficits in adaptive functioning (Turk & Graham, 1997), and greater deficits in socialisation (Hernandez et al, 2009) in those with comorbid ASD when compared to those with FRAX only. This research suggests that presence of comorbid ASD in FRAX may result in a poorer prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…48 The Fmrp (fragile X mental retardation protein)-deficient mouse, a model for FXS, exhibits marked susceptibility to audiogenic seizures [49][50][51] and evidences the enlarged testes, although not the facial dysmorphology, characteristic of the human disease. [51][52][53][54] Most studies report that the loss of Fmrp in mice does not lead to overt motor impairment, severe learning deficiencies, or a lack of social approach.…”
Section: Mouse Models Of Genetic Clinical Disorders With Autism Symptmentioning
confidence: 99%
“…Among these, fragile X linked mental retardation is the most common. The incidence of the association of fragile-X with autism ranges from 14% or less to 47% (14,15).…”
Section: The Characterization Of a Fragile X Induction Systemmentioning
confidence: 99%